599 Exploring Ways to Optimize Parental Involvement in Adolescent Sleep Interventions. (3rd May 2021) - Zoltanski, Ava; Levenson, Jessica; Reyes, Zoe; Bahary, Sigalle; Ford, Hannah; Patel, Garima; Miller, Elizabeth; Mukundan, Aishwarya
Abstract: Introduction: Sleep is critical to the health and functioning of adolescents, but most teens do not obtain the recommended amount of sleep each night. Some sleep interventions have been efficacious in promoting sleep among adolescents, though others have had a more limited impact. One potential strategy for improving the efficacy of adolescent sleep promotion programs is to optimize the role of parents in supporting their child's sleep. Recent findings on parental involvement in adolescent sleep suggest that monitoring can improve sleep duration but may be challenged by disagreements about sleep between parents and adolescents. Thus, it is crucial to understand how to involve parents in adolescent sleep promotion while supporting adolescent autonomy. Here, we report qualitative data on strategies for involving parents in adolescent sleep promotion in a way that is acceptable and effective. This data was collected specifically to inform the development of a sleep promotion program for adolescents. Methods: We conducted 9 focus groups (3 each for youth, parents of adolescents, and healthcare providers treating adolescents). Transcripts of focus group proceedings were coded and thematically analyzed using inductive and deductive approaches, focusing on parents' current role in their child's sleep and the proposed role of parents in an adolescent sleep program. Results: Some parents report being involved in their child's sleep habits by setting bedtimes and supervising a consistent sleep routine. Adolescents prefer parental support that encourages child autonomy for their own sleep routine. To maintain healthy sleep habits, parents report that physicians or other trusted adults may play a key role in facilitating the negotiation of sleep habits that addresses the priorities of both parents and adolescents. Conclusion: Our findings support adolescent preference for autonomy in their health behaviors consistent with their developing independence during this development period. Future work should focus on improved understanding of how adolescents and parents can negotiate adolescent autonomy and should examine the efficacy of a sleep promotion program based on varying levels of parental involvement. Support (if any):